2018
DOI: 10.1155/2018/1673517
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Antenatal Healthcare Utilisation by Pregnant Women in Third Trimester in Peri-Urban Ghana

Abstract: Access to quality healthcare still remains a major challenge in the efforts at reversing maternal morbidity and mortality. Despite the availability of established maternal health interventions, the health of the expectant mother and the unborn child remains poor due to low utilisation of interventions. The study examined the socioeconomic determinants of antenatal care utilisation in peri-urban Ghana using pregnant women who are in their third trimester. Two-stage sampling technique was used to sample 200 preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
60
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 34 publications
20
60
4
3
Order By: Relevance
“…The result was not consistant with others. Fawcus SR et al 9 and Chigbu B et al 10 , Akowuah et al 11 showed that a higher percentage of unbooked mothers belonged to lower socio-economic status. The poor economic and education status may make it difficult for women to make informed decisions about using preventive and promotive health services, such as antenatal care.…”
Section: Discussionmentioning
confidence: 97%
“…The result was not consistant with others. Fawcus SR et al 9 and Chigbu B et al 10 , Akowuah et al 11 showed that a higher percentage of unbooked mothers belonged to lower socio-economic status. The poor economic and education status may make it difficult for women to make informed decisions about using preventive and promotive health services, such as antenatal care.…”
Section: Discussionmentioning
confidence: 97%
“…Among women, accessing health information from religious‐based programs, higher‐level government facilities, and primary healthcare facilities ensured good knowledge about HBV transmission. Given the general deprivation of the UWR, which is also predominantly rural, government health facilities, including CHPS, clinics, and hospitals mandated to create HBV awareness, have incorporated health information sessions as part of neonatal care services 32,33 . Expectant mothers visiting these health facilities for antenatal health services are required to undergo mandatory health information sessions where they may acquire knowledge about HBV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the husband education has the similar impact on the utilization of reproductive and maternity cares. Evidence indicate that men with higher education are more likely to contribute to the reproductive needs of their partner (23,26).…”
Section: Discussionmentioning
confidence: 99%